Clinical outcomes associated with anti-CD38-based retreatment in relapsed/refractory multiple myeloma: a systematic literature review - Gay, Francesca; Zamagni, Elena; Cole, Craig Emmitt; Scheid, Christof; Hultcrantz, Malin; Chorazy, Justyna; Iheanacho, Ike; Pandey, Anuja; Bitetti, Jacopo; Boytsov, Natalie; Purser, Molly; McNamara, Simon; et al. (Frontiers in Oncology, 2025)
IntroductionAnti-CD38-based therapy has become a backbone regimen for the treatment of multiple myeloma (MM), approved in first-, second-, and third-line settings. The effectiveness of anti-CD38-based retreatment after an initial relapse on previous anti-CD38-based therapy is unclear. Here we present the results of a systematic literature review investigating the clinical outcomes of anti-CD38-based retreatment in patients with relapsed/refractory MM.MethodsMedline/Embase, congress publications, and other sources were searched (to December 8, 2023) for relevant articles in English and screened for eligibility criteria using the Population, Intervention, Comparator, Outcomes, Study Design (PICOS) framework, and data were then extracted for outcomes including progression-free survival (PFS), overall survival (OS), and overall response rate (ORR).ResultsIn total, 2938 records were identified from the initial Medline/Embase search and 11 were identified from other sources; 34 were eligible for inclusion, representing 24 studies (6 clinical [n=18–307] and 18 real-world evidence [RWE; n=19–583]). Where reported, median follow-up ranged from 1.9–43.0 months across 6 clinical and 8.7–53.0 months across 10 RWE studies. For clinical trials, anti-CD38-based retreatment resulted in a median PFS of 1.0–2.8 months in all but one trial (19.4 months), a median OS of 10.7–19.1 months (not reached in one trial), and ORRs of 0–75%. RWE studies reported a median PFS of 1.5–8.4 months, a median OS of 8.4–19.0 months (not reached in one study), and ORRs of 24.6–90.0%.DiscussionFindings from this systematic literature review indicate that clinical outcomes with anti-CD38-based retreatment are variable and offer limited clinical benefit in patients with relapsed/refractory MM, including in those refractory to anti-CD38-based treatment.